Deregulating Naloxone to Combat Opioid-Related Overdoses in British Columbia: The Potential Moral Hazard of a Progressive Harm Reduction Policy - Kody Crowell (McMaster University Library Press, 2019)
British Columbia fully unscheduled the opioid overdose-reversing drug known as naloxone on 21 September 2016 in an attempt to reduce opioid overdose-related mortality. Having a large population of injectable drug users, the move represents just one harm reduction initiative out of many the province has executed over the years. The change was intended to remove any regulatory barriers to the drug, thereby granting users, their peers, and public health organizations greater access. Given the devastating impacts of the opioid crisis in North America, particularly the Western coast, the political climate favoured the quick and unopposed implementation of this reform. The move was supported by physicians and pharmacists alike, who recognized the importance of harm reduction strategies alongside the availability of proper training. While no evaluation has been completed, anecdotal evidence from paramedics has suggested that illicit, off-label uses of naloxone are on the rise, posing a potential moral hazard of increased availability.